FOOD IDIOMS IN ENGLISH: A LINGUACULTURAL APPROACH - Makhmudova Sabinabonu (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation.  This  text  introduces  the  Linguocultural  Approach  to  language study,  emphasizing  the  inseparable  connection  between  language  and  culture.  It defines language as both a product and shaper of culture, highlighting how it embodies cultural values, beliefs, and history. The approach focuses on the cultural background reflected  in  linguistic  units  and  precedent  texts.  The  text  stresses  the  critical importance of this approach for understanding idioms, which are presented as deeply embedded in cultural contexts and history. It defines idioms as figurative expressions whose meaning differs from the literal words. The text then specifically applies the linguocultural  approach  to  English  food  idioms,  detailing  how  to  examine  their cultural origin, embedded values, the link between literal and figurative meanings, and cross-cultural comparisons.